The Influence of Natural Bayah Zeolite on the Pyrolysis Process of Liquid Fuel Based on HDPE and PP Plastic Waste - Heriyanto, Heri; Suhendi, Endang; Nasheh, Muhammad Yusril; Rizqillah, Muhammad Fathi; Wardalia, Wardalia; Pujiastuti, Hendrini (World Chemical Engineering Journal, 2024)
Pyrolysis is a decomposition reaction method involving the heating of a material with little or no oxygen. The objectives of this research are to utilize plastic waste for the production of liquid fuel and determine the optimal conditions for maximizing liquid fuel yield. The pyrolysis method was used at a temperature of 350°C for 300 minutes with High-Density Polyethylene (HDPE) and Polypropylene (PP) plastic as raw materials in composition variations of 7:3, 5:5, and 3:7, and the Bayah natural zeolite catalyst was activated and varied in amounts of 0%, 3%, and 5%. The analysis included yield tests, density tests, viscosity tests, calorific value tests, and the composition analysis of the liquid product yield.The results of this research indicated that the highest liquid product yield was obtained with a composition of 30% HDPE, 70% PP, and 0% catalyst, achieving a yield of 66.4%. It was concluded that the activated Bayah natural zeolite catalyst was not sufficiently effective in the pyrolysis process at a temperature of 300°C. The highest density and viscosity values were obtained with a composition of 70% HDPE, 30% PP, and 0% catalyst, which were 0.764 g/cm³ and 0.789 cP, respectively. The highest calorific value was obtained with a 50% HDPE and 50% PP composition, reaching 10,978.8 Cal/g. The composition analysis of the liquid product yield for a 70% HDPE and 30% PP composition resulted in 42% gasoline and 58% kerosene. For a 30% HDPE and 70% PP composition, the yield was 30% gasoline, 62% kerosene, and 8% diesel.